Characteristics associated with confidence in the vaccine for COVID-19 in citizens of La Libertad - YUPARI AZABACHE, Irma Luz (2021)
Introduction: The presence of COVID-19 generated a socio-economic and public health crisis worldwide, the only alternative to counteract this virus, in addition to all health measures, is the application of a vaccine to the entire population; However, it is known that to promote confidence in the effectiveness of vaccines it was not enough to provide information in this regard, but also to know other factors that influence it; For this reason, the present research had the objective of analyzing the characteristics associated with confidence in the vaccine in citizens of the department of La Libertad in the year 2021. Method: A cross-sectional, correlational design was applied; A questionnaire was carried out and the data were collected using a virtual form from 284 citizens, whose sample was found with an error of 5.8%. Results: The findings indicate that 61.3% of citizens do trust the effectiveness of vaccines for COVID-19. Analyzing the biological characteristics, the elderly are those who have the greatest confidence in the effectiveness of the vaccines (100% of respondents), and the male sex (76.7%). In family characteristics, single people (62.3%) and who have children (65.9%). In social characteristics, having primary or secondary education (69%) and stable work (66%), as well as the virus not having been affected by this virus (64.6%), contribute to a greater acceptance of the vaccine against SARS COV 2 Conclusions: Of the analyzed characteristics, sex and having children are those that are related to confidence in the effectiveness of the vaccine.Keywords: Vaccine, Effectiveness, confidence, COVID-19.